The centuries-old dialogue between Buddhism and Christianity - Clasquin-Johnson, M. (Faculty of Theology, University of the Free State, 2009)
This article examines the pre-history of today’s dialogue between Buddhists and Christians. Contrary to what one might think, pre-modern Europeans did have some understanding of Buddhism, however limited and distorted it might have been. Asians during the same period had a far better chance of understanding Christianity, because of the widespread presence of the Nestorian Church from Arabia to China. We do have evidence that interaction between Buddhists and Christians lead to some creative synthesis between the two.
Keywords: Buddhism; Christianity; Interreligious dialogue